CutTheTail: An Accurate and Space-Efficient Heuristic Algorithm for Influence Maximization. (23rd June 2020) - Popova, Diana; Kawarabayashi, Ken-ichi; Thomo, Alex
Abstract: Algorithmic problem of computing the most influential nodes in an arbitrary graph (influence maximization) is an important theoretical and practical problem and has been extensively studied for decades. For massive graphs (e.g. modelling huge social networks), randomized algorithms are the answer as the exact computation is prohibitively complex, both for runtime and space. This paper concentrates on developing new accurate and efficient randomized algorithms that drastically cut the memory footprint and scale up the computation of the most influential nodes. Implementing the Reverse Influence Sampling method proposed by Borgs, Brautbar, Chayes and Lucier in 2013, we engineered a novel algorithm, CutTheTail (CTT), which solves the problem of influence maximization (IM) while using up to five orders of magnitude smaller space than the existing renown algorithms. CTT is a heuristic algorithm. We tested the accuracy of CTT on large real-world graphs using Monte Carlo simulation as the benchmark and comparing the quality of CTT solution to the algorithms with theoretically proven guaranteed approximation to optimal. Experiments show that CTT provides solutions with the quality equal to the quality of such algorithms. Savings in required space allow to successfully run CTT on a consumer-grade laptop for a graph with almost a billion of edges. To the best of our knowledge, no other IM algorithm can compute a solution on such a scale using a 16 GB RAM laptop.